2021
DOI: 10.1111/exsy.12667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial intelligence on English speaking anxiety and speaking performance: A case study

Abstract: Foreign language anxiety (FLA) has been a perennial concern in language learning, as foreign language (FL) learners often communicate feelings of anxiety, stress, or nervousness. This study explored the role of artificial intelligence (AI) applications in speaking practice for FLA management of 48 undergraduate participants in an EFL class in Egypt. An eight‐week, quasi‐experimental pretest–posttest design examined learner anxiety levels using a 33‐item FLA questionnaire. Their oral proficiency was assessed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 49 publications
(169 reference statements)
2
31
0
Order By: Relevance
“…For the first correlation, it was revealed that self-efficacy showed a strongly positive correlation to learners' speaking performance. This finding echoed a number of previous studies (Anyadubalu, 2010;El Shazly, 2021;Erkan & Saban, 2011;Li & Wang, 2010;Quinto & MacAyan, 2020;Sabti et al, 2019;Tridinanti, 2018). This implies that it is inevitable that self-efficacy be cultivated to increase learners' English performance, particularly speaking.…”
Section: Self-efficacy and Speaking Performancesupporting
confidence: 77%
See 1 more Smart Citation
“…For the first correlation, it was revealed that self-efficacy showed a strongly positive correlation to learners' speaking performance. This finding echoed a number of previous studies (Anyadubalu, 2010;El Shazly, 2021;Erkan & Saban, 2011;Li & Wang, 2010;Quinto & MacAyan, 2020;Sabti et al, 2019;Tridinanti, 2018). This implies that it is inevitable that self-efficacy be cultivated to increase learners' English performance, particularly speaking.…”
Section: Self-efficacy and Speaking Performancesupporting
confidence: 77%
“…English learners use four skills to learn English: listening, speaking, reading, and writing. In order to achieve the aim of learning English, speaking ability is the most important in communicating and provides several problems (El Shazly, 2021;Le & Nguyen, 2021;Tridinanti, 2018). They are nervous when they are learning to talk.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review on conversational AI in language education, the authors found that there are five main applications of conversational AI during teaching [22], the most common one being the use of large language models as a conversational partner in a written or oral form, e.g., in the context of a task-oriented dialogue that provides language practice opportunities such as pronunciation [23]. Another application is to support students when they experience foreign language learning anxiety [24] or have a lower willingness to communicate [25].…”
Section: Review Of Research Applying Large Languagementioning
confidence: 99%
“…At the 2010 American Society for Supervision and Curriculum Development seminar on personalized learning, participants reached a consensus on five basic elements of personalized learning, namely, flexible learning time and space, reshaping teacher roles, and task-based inquiry learning, custom learning path, and custom learning pace [15]. The Bill & Melinda Gates Foundation and other organizations believe that the implementation of personalized learning should rely on electronic school bags, customized paths, free environment, and the support of competitiveness [16].…”
Section: Introductionmentioning
confidence: 99%